Digital technology and democratic theory - Bernholz, Lucy; Landemore, Hélène; Reich, Rob (Chicago ; London : University of Chicago Press, 2021)
"One of the most far-reaching transformations in our era is the wave of digital technologies rolling over-and upending-nearly every aspect of life. Work and leisure, family and friendship, community and citizenship-all transformed by now-ubiquitous digital tools and platforms. Digital Technology and Democratic Theory explores a particularly unsettling and rapidly evolving facet of our new digital lives: transformations that affect our lives as citizens and participants in democratic governments. To understand these transformations, scholars from multiple disciplines (computer science, philosophy, political science, economics, history, and media and communications/journalism) wrestle with the question of how digital technologies shape, reshape, and affect fundamental questions about democracy and democratic theory. The contributors consider what democratic theory-broadly defined as normative theorizing about the values and institutional design of democracy-can bring to the practice of digital technologies. From the connectivity and transmission of information that has inspired positive change through movements such as the Arab Spring and #MeToo to the nefarious spread of distrust and outright disruption in democratic processes, this volume broaches the most pressing technological changes and issues facing not just individual states, but democracy as a philosophy and institution"-- "One of the most far-reaching transformations in our era is the wave of digital technologies rolling over-and upending-nearly every aspect of life. Work and leisure, family and friendship, community and citizenship-all transformed by now-ubiquitous digital tools and platforms. Digital Technology and Democratic Theory explores a particularly unsettling and rapidly evolving facet of our new digital lives: transformations that affect our lives as citizens and participants in democratic governments. To understand these transformations, scholars from multiple disciplines (computer science, philosophy, political science, economics, history, and media and communications/journalism) wrestle with the question of how digital technologies shape, reshape, and affect fundamental questions about democracy and democratic theory. The contributors consider what democratic theory-broadly defined as normative theorizing about the values and institutional design of democracy-can bring to the practice of digital technologies. From the connectivity and transmission of information that has inspired positive change through movements such as the Arab Spring and #MeToo to the nefarious spread of distrust and outright disruption in democratic processes, this volume broaches the most pressing technological changes and issues facing not just individual states, but democracy as a philosophy and institution"--